(untitled) (Brazilian Journal of Health Research, 2023)
Introduction: Covid-19 is an infectious disease caused by the SARS-Cov-2 virus, which generates a severe acute respiratory syndrome, and which led to a current pandemic that started in 2020, with unprecedented morbidity and mortality. Despite everything that is known about the treatment of SARS-Cov-2 and the vaccines produced, there are still a high number of deaths due to issues that are not related to the vaccine, but mainly regarding cardiovascular events. Objectives: The objective of this research is to evaluate whether the drug treatment used is the correct one and the positive effect expected, demystifying the questions raised by the media about the beneficial effects of vaccines. Methods: This is a Systematic Review, for which 15 articles were selected from the U.S. National Library of Medicine and the National Institutes of Health (PubMed) and Virtual Health Library (BVS). Results: The publications demonstrated that the cardiovascular problems observed in patients with SARS-Cov-2 are due to the physiopathology of the disease and patients’ treatment, shifting the responsibility of vaccines for such feats. Conclusion: it is concluded that effective treatment must be instituted to avoid thromboembolism and ischemic events due to Covid-19 and vaccination must be incentivized.